The effectiveness of transcranial magnetic stimulation for dysphagia in stroke patients: an umbrella review of systematic reviews and meta-analyses - Georgiou, Anastasios M.; Phylactou, Phivos; Kambanaros, Maria (Frontiers in Human Neuroscience, 2024)
Numerous studies have explored the use of repetitive Transcranial Magnetic Stimulation (rTMS) intervention in post-stroke dysphagia. The primary aim of this umbrella review was to appraise the methodological quality of systematic reviews (SRs), with and without meta-analyses (MAs), that synthesized the findings of randomized controlled trials (RCTs) exploring the effectiveness of rTMS in the management of dysphagia post-stroke. A secondary aim of this study was to evaluate the consistency and reliability of translational implications of rTMS for swallowing recovery after stroke across these SRs and MAs. We searched several databases from inception to the 14th of May 2023, to identify SRs and MAs that examined the effectiveness of rTMS in the management of dysphagia post-stroke. The methodological quality of the included studies was evaluated utilizing the AMSTAR 2 (A Measurement Tool to Assess Systematic Reviews) instrument. To investigate the extent of literature overlap among the primary studies included in the SRs, the Graphical Overview of Evidence (GROOVE) was utilized. Of the 19 SRs that were identified, two studies received low quality ratings, while the rest (17) were rated with critically low quality based on the AMSTAR 2 rating. A high literature overlap across the SRs was observed. In all SRs and MAs reviewed, there was a consistent presence of at least some significant evidence supporting the effectiveness of rTMS in enhancing swallowing outcomes for individuals with dysphagia post-stroke, that is, all MAs reported at least a moderate overall effect in favor of rTMS (SMD range = [0.59, 6.23]). While rTMS shows promise for improving dysphagia post-stroke, the current evidence remains limited and inconclusive due to the methodological flaws observed in the published SRs and their respective MAs on the topic so far. Concerning the limitations of our study, language restrictions and methodological shortcomings may affect the generalizability of our findings.